Integration of Local Taxes and Public Value: A Strategy To Increase Public Participation - Eko Aryansah, Januar; Lionardo, Andries; Budiyanto, M Nur; Ghoffar Ismail, Rizky (Iapa Proceedings Conference, 2024)
This study aims to examine integration strategies between local taxes and public values to increase public participation in tax payments. Local taxes are an important source of revenue for local governments for regional development and public services. However, low public participation in tax payments remains a major challenge for many regions. This approach proposes the incorporation of public values, such as transparency, accountability, and social inclusion, in local tax management to build public trust. Through a mixed method involving surveys and interviews, this study explores how the application of public values in local tax policies can strengthen citizen engagement in fulfilling their tax obligations. The results show that the integration of public values is able to increase public tax awareness and compliance, as well as have a positive impact on regional development. Therefore, it is recommended for local governments to prioritize public value-based strategies as an effort to increase tax participation in order to realize shared prosperity.